HUBUNGAN ANTARA PERSEPSI TERHADAP HARGA DAN KUALITAS PRODUK DENGAN MINAT MEMBELI PRODUK FASHION ONLINESHOP DI FACEBOOK PADA MAHASISWA POLITEKNIK X SEMARANG - Nurtjahjanti, Harlina (Jurnal Psikologi, 2012)
Trust in the online shop on facebook was expected to affect the interest of consumers in buying. Products offered on online fashion shop cannot be touched and and thus require a high enough trust to buy via online shop. This study aims to examine the relationship between the perception of price and quality of products with interest in buying products through online fashion shop on facebook at a polytechnic university in Semarang. The research samples were 60 students which were analysed by using multiple regression analysis. The result of first hypothesis showed that the perception of price was related positively and significantly to interest in buying products through online fashion shop on facebook as shown in rxy= 0,934, sig= 0,000 (Î±=0,05). The second hypothesis test showed that quality of products was not significant with interest in buying products through online fashion shop on facebook with rxy= 0,063 sig= 0,480 (Î±=0,05). Third hypothesis test also showed that the perception of price and quality of products simultaneously had positive and significat impact on the interest in buying products through online fashion shop on facebook rxy = 0,708, sig= 0,000 (Î±=0,05). Test result also showed that R2 = 0,501.Keywords: Interest in buying products, online fashion shop on facebook, perceived of price, quality of products.